Pelatihan Pemanfaatan Internet Sehat Bagi Masyarakat Desa Cibinuang Kabupaten Kuningan - Tito Sugiharto; Tata Sutabri; Panji Novantara; Roni Nursyamsu; Rio Priantama (Cv. Utility Project Solution, 2022)
Internet Safety is one of the concepts in utilizing and using Internet technology to protect oneself from possible risks or dangers in the digital world. The growing internet affects all areas of life both in cities and in villages. Cibinuang Village is one of the villages in Kuningan district where the majority of the people are farmers. Currently the people of Cibinuang village are starting to recognize and use the Internet in their daily lives. Based on a survey on Internet usage by the people of Cibinuang Village, they are still using it to find information, watch entertainment, play games and social media. There are problems in the use of the Internet in society, namely that people are vulnerable to receiving false information or hoaxes, school children are addicted to playing online games without a time limit, the use of social media is not optimal. The purpose of this Internet Safety utilization training activity is to provide knowledge and insight about the benefits and dangers of the digital world. So that with this training the people of Cibinuang village can be wise and careful in using the Internet. The partners of this activity are the apparatus and the Cibinuang village community. The training method is carried out with presentations and demonstrations on Internet Safety . The results of this activity are increasing public insight and knowledge regarding the use of Internet Safety